दि बड’नि खनसायनाय रायथाइमाला - (:unkn) unknown (Bodo Publication Board Bodo Sahitya Sabha, 2012)
The Bodoni Khansaynay Raythaimala is a collection articles gleaned from various issues of the Bodo. This is a yearly mouth piece of the Bodo Sahitya Sabha, written by different Bodo writers since 1956 till the present day.
The Bodoni Khansaynay Raythaimala
Keywords: Bodo; Literature; Bodo; Bodo